On anarchism : dispatches from the people's republic of Vermont - Van Deusen, David, 1973- (Algora Publishing, 2017)
The contemporary anarchist world, including the idea of secession as it flourishes in ""Bernie Sanders' Vermont, "" is outlined in these collected writings of an AFL-CIO union officer, laborer, journalist and anarchist organizer. With a partial focus on the Green Mountain Anarchist Collective but applicable throughout the US, he describes political goals and specific events in the last few decades; central to the theme is the aim to expand venues for democratic decision making and socialism.